Integrated approaches to manage the invasive alien weed Parthenium in Northern Sri Lanka - Kishojini, P.; Pakeerathan, K.; Mikunthan, G. (IOBC Newsletter, 2017)
Family Asteraceae member Parthenium hysterophorus is one of the noxious alien weeds to Sri Lanka, invaded from India and spread from Vavuniya to all over the country within a short period of time using its own biologicalpower. Parthenium weed is a resilient plant; therefore it can grow in wide range of soils and climatic conditions.It can grow in wastelands, agricultural areas, shrub lands, urban areas, overgrazed pastures and along roadsides,industrial areas, playgrounds, railway tracks and residential developments. Individual plants can produce up to 100,000 seeds each in their lifetime and seeds germinate anytime moisture is available. Seeds can disperse over long distance through wind, machinery, livestock, livestock feed, vehiclesmovement and water currents. This noxious weed has the potential to cause serious economic loss in crop production and environmental human health hazards issues such as, dermatitis, asthma and bronchitis.